PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 005 RAJA BEJAMU KACAMATAN SINABOI - Julia Mentari Fitri; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of the problem from this research is that students do not understand about science lessons. Researchers conducted this research in two cycles, Cycle I consisted of two meetings with two Learning Plan (RPP), two Student Worksheets (LKS) and daily repetition I, while cycle II consisted of two meetings with two Learning Implementation Plans (RPP), two Student Worksheets (LKS) and daily test II. The data obtained through the observation sheet and the science lecture test were then analyzed. From the average data analyzed analyzed obtained teacher activity in implementing learning increased from 78,57% with good category in cycle I become 91,07% with good category once in cycle II. The average of student learning activity in learning has increased from 60% with good category in cycle I to 75% with good category once in cycle II. both individually and classically increased in cycle I of 20 students (80%) complete and students are not complete 6 students (20%). While in cycle II, there are 25 students (95%) and students who are not complete 1 students (5%). The average score of students score in cycle I is 68.27 while in cycle II is 80.19.Key word: Contextual teaching and learning (CTL), Students outcome.